(untitled) (Edma 0-6: Educación Matemática en la Infancia, 2021)
This study presents the design, construction and validation of the rubric “Acquisition of important mathematical knowledge between 3 and 6 years old” (AIMK 3-6). In order to design and construct the rubric, six phases have been considered: historical-epistemological analysis of the mathematical content standards (Early Algebra, Number and Operations, Geometry, Measurement, Data Analysis and Probability), its meanings and its presence in international and national curricular guidelines of the early ages; 2) research on important Mathematics from 3 to 6 years; 3) construction of the pilot version of the instrument; 4) validation through expert judgment; 5) construction of the final version; and 6) pilot test with Preschool teachers. Specifically, six experts in early childhood mathematics education and six Preschool teachers have assessed the fitness, formulation and pertinence of the elements of the rubric. As a result of this assessment, some indicators and items have been incorporated, removed or modified in order to construct the definitive rubric, which aims to serve as both an evaluation tool and a guidance tool for Preschool teachers.